The determinants of smes’ firm performance in lampung province, indonesia - Jayanagara, Oscar (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to study the influence of the Strategic Orientation of Entrepreneurship and Organizational Culture on Innovation, and its implications for the performance of Micro, Small and Medium Enterprises. This research is a conclusive research conducted through data collection using descriptive and causality surveys. This research was conducted with a sample of 420 micro, small and medium enterprises in Lampung Province, Indonesia. The results of this study are the Effect of Mediation on Innovation Increasing the Effect of Entrepreneurship Strategic Orientation and Organizational Culture on the Performance of Small and Medium Enterprises. The results of this study generally have an influence on the Strategic Orientation of Entrepreneurship and Organizational Culture on the Performance of SMEs. The seven hypotheses proposed in this study are all acceptable. Organizational Culture as an independent variable has the strongest influence on SME Innovation and Performance. This dissertation also provides a discussion of the findings and limitations, theoretical and practical contributions, theoretical and managerial implications of research, and suggestions for future research.